The Role of Cosmic Rays in the Modulation of Lower Atmosphere Temperature (Bulletin of Pure and Applied Sciences – Physics, 2021)
Observational evidences suggest that there is an apparent relationship between solar  variability and the lower atmosphere. The assumption made in climate models that the  variation in solar radiation can explain observed variations in the lower atmosphere is not  entirely true. Past studies suggest that cosmic rays of both galactic and solar origin might be  responsible for temperature change in the lower atmosphere. It is a fact that solar cycle is  strongly correlated with the cosmic ray flux therefore it is desirable to search the physical  mechanisms which mediate between solar activity and the global temperature. It is suggested  that the observed variation in cloud cover might provide a possible link between varying solar  activity and global temperature. Some other mechanisms might also be playing their roles in  modulating the earth’s atmospheric processes. In this research article, we have attempted to  explain how cosmic rays could modify the terrestrial temperature.